The Spanish immigrants in Brazilian literature - Nascimento, José Leonardo do (Universidade Estadual Paulista / UNESP, 2009)
Concerning the immigratory phenomenon, the paper presents the enigma of "invisibility" related to the large number of Spanish people in the Brazilian society, settled in the State of São Paulo mainly during the First Republic. The analysis concentrates on the Brazilian literature texts that stressed the presence of Spanish characters.